Desain Modul Ajar Berbasis Kearifan Lokal untuk Memperkuat Karakter Pelajar Pancasila - Suleha Ecca (Scholaria: Jurnal Pendidikan dan Kebudayaan)
Integrating local wisdom into Indonesian language learning can enhance students' love and pride in their own culture while helping them understand the values embedded within it. This research employed a qualitative descriptive method aimed at analyzing the needs of students and teachers for teaching materials based on local wisdom in the subject responding to and analyzing texts. Research data were collected through surveys using questionnaires and interviews with seventh-grade students and Indonesian language teachers at SMP Muhammadiyah Rappang. The results showed that both students and teachers agreed on the integration of local wisdom to improve understanding of the learning material. The local wisdom concepts identified as essential are Sipakatau, Sipakalebbi, and Sipakainge. The preferred types of teaching materials include both print and electronic formats. Therefore, it is recommended to design and develop teaching materials based on local wisdom to support character development aligned with the Pancasila Student Profile framework. In conclusion, integrating local wisdom into teaching materials for responding to and analyzing texts is a crucial need to enrich students' learning experiences and foster character development rooted in cultural values and Pancasila principles.